A computer‐aided framework for product design with application to wheat straw polypropylene composites. (20th October 2015) - Fatoni, Rois; Elkamel, Ali; Simon, Leonardo; Almansoori, Ali
Abstract: The use of wheat straw and other agricultural byproduct fibres in polymer composite materials offers many economic and environmental benefits. Wheat straw has been recently commercialized as a new filler for polypropylene thermoplastic composites in automotive applications. However, to expand its application in the automotive industry and other sectors where highly‐engineered materials are needed, a systematic database and reliable composite property models are needed. For this purpose, this research aims to develop a product design approach based on mixture design methodologies and inverse optimization for wheat straw polypropylene (WS‐PP) composites for the automotive industry. The approach follows hierarchical steps starting from consumer needs and ending with specific end‐products. Relevant information obtained systematically from historical data is used to design experiments and develop response surface models of composite properties as a function of a composite's component proportion. The response surface models are used to simulate and optimize the composition formulation of the composite, which meets the targeted product specifications. The last step of the proposed methodology is to optimize the composite ingredients to maximize wheat straw utilization in the final composite while minimizing the overall material cost. A case study is presented for the design of wheat straw polypropylene/impact copolymer polypropylene (WS‐PP/ICP) composite for the automotive industry.